Novel Proteome and N-Glycoproteome of the Thermophilic Fungus Chaetomium thermophilum in Response to High Temperature - Gao, Jinpeng; Li, Qingchao; Li, Duochuan (Frontiers in Microbiology, 2021)
Thermophilic fungi are eukaryotic species that grow at high temperatures, but little is known about the underlying basis of thermophily at cell and molecular levels. Here the proteome and N-glycoproteome of Chaetomium thermophilum at varying culture temperatures (30℃, 50℃, and 55℃) were studied using hydrophilic interaction liquid chromatography enrichment and high-resolution liquid chromatography–tandem mass spectroscopy analysis. With respect to the proteome, the numbers of differentially expressed proteins were 1274, 1374, and 1063 in T50/T30, T55/T30, and T55/T50, respectively. The up-regulated proteins were involved in biological processes, such as protein folding and carbohydrate metabolism. Most down-regulated proteins were involved in molecular functions, such as structural constituent of the ribosome and structural activity. For N-glycoproteome, the numbers of differentially expressed N-glycoproteins were 160, 176, and 128 in T50/T30, T55/T30, and T55/T50, respectively. The differential glycoproteins were mainly involved in various types of N-glycan biosynthesis, mRNA surveillance pathway, and protein processing in the endoplasmic reticulum. These results indicated that an efficient protein homeostasis pathway plays an essential role in the thermophily of C. thermophilum, and N-glycosylation is involved by affecting related proteins. This is the novel study to reveal thermophilic fungi's physiological response to high-temperature adaptation using omics analysis, facilitating the exploration of the thermophily mechanism of thermophilic fungi.